Correlation of patient-specific QA systems between Delta4 and PerFRACTION for head and neck cancer with volumetric modulated arc therapy technique at Rajavithi Hospital - Prommoon, Wararat (The Thai Journal of Radiological Technology, 2024)
Introduction: Patient-specific quality assurance (PSQA) is essential for the Volumetric Modulated Arc Therapy (VMAT) plan. Objective: The objective of this study was to determine the correlation of gamma passing rate results between two PSQA tools, Delta4 and PerFRACTION, for head and neck cancer plans at Rajavithi Hospital. Materials and Methods: The gamma passing rate data of PSQA for head and neck cancer of 50 patients with Delta4 and PerFRACTION measurements from the Elekta Versa HD at 6 MV photon beam were collected. Results: The mean gamma passing rate and standard deviation by Delta4 were 98.01±1.09. The comparison results of Delta4 data with PerFRACTION, showed good, better, and best with the overall mean gamma passing rate of 96.86±0.90, 98.01±0.77, and 99.08±0.58, respectively. The Pearson’s correlation was 0.73 (p-value <0.01). Conclusion: The results from Delta4 and PerFRACTION demonstrate good agreement and correlation, confirming the compatibility of both PSQA systems.